Awareness and Preventive Practices regarding Dengue among Community Adults: A Cross-sectional Study - Poudel, Bimala; Bhandari, Bhawana; Nembang, Tina (Journal of Advanced Academic Research, 2024)
Dengue viruses spread to people through the bites of an infected Aedes mosquito (A.aegypti or A. albopictus). Almost half the world’s population, about 4 billion people, lives in areas at risk of dengue. This study aimed to assess the awareness and practices regarding dengue among adult people in a selected community of Jhapa, Nepal. A descriptive cross-sectional study was used. A total of 101 samples were selected using the non-probability convenience sampling technique. A self-developed structured interview schedule was used to collect data. Data analyses were done in Statistical Package of Social Science version 20. Descriptive and inferential statistics namely the Chi-square test were used to analyze the data. The majority of respondents i.e., 63.4% were aware of dengue while more than half of the respondents i.e. 54.5% had poor practices on dengue prevention. There was a significant association between age, ethnicity, and occupation with awareness of dengue. Likewise, ethnicity and occupation had a significant association with practices of dengue prevention among respondents. The study highlights the importance of improving dengue prevention practices and awareness, emphasizing the need for targeted efforts based on age, ethnicity, and occupation.